Translating the Transcends of God's World in the Arabic-Quran into Balinese - Efri Arsyad Rizal; Mohamad Sobirin (UIN Sunan Kalijaga Yogyakarta, 2021)
The development of Quranic translation in Indonesia generally showed the total adoption of the fixed theological words and phrases of the Arabic-Qur’an as loanword in the translation work. For some local communities, it does not make them easier in understanding the messages of the Quran through its “untranslated” words and phrases. So, some parties within Muslim communities tried to translate them using the local language. Cakepan Suci Al-Qur'an Salinan Ring Basa Bali by I Wayan Rupa Mengwi is one of the Qur’an translation into local languages, it is the first Balinese translation of the Qur’an, which prefer to translate them rather than to borrow them in translation. But it remains questions how the author vernacularized some “fixed theological terms and phrases” of the Arabic-Qur’an into Balinese and why did he chose to “translate” them rather than to “borrow” them in his translation work? The result showed that (1) it used terminological approach to vernacularize some fixed terms and phrases, (2) The special appeal of using Balinese words and phrases when translating selected Qur'anic words and phrases is to reflect typical local beliefs (Balinese), as well as to carry out da'wah through a socio-cultural approach. Even though, this pattern reflects the platform and strategy of international Ahmadiyya movement through the translation of the Qur'an, but this work is not connected formally under the organization program of Ahmadiyya.